Pengembangan Teknologi Informasi di Dunia Kesehatan dan Pendidikan - Katulistiwa, Nariyah Koriyota; Nata Dirgantara Putra Wahdana; Nitya Nabilah Nariswari; Nur Diana Hamidah; Nur Mufidah (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2022)
The development of technology and information is common in the digital age. Online media as a form of sophistication of information and communication technology plays a big role in human life, one of which is in improving health services. Based on the background above researchers are interested in conducting this study entitled "Development of Information Technology in the World of Health and Education". This study uses a method of review literature. In this study obtained results that there are various examples of the use of technology in health such as halodokter websites used in counseling and credible sources of health information, in addition to the development of technology requires nurses to be able to compensate with the level of technology that exists by increasing knowledge and sharing knowledge of fellow nurses. In education virtual simulation plays a role in mental nursing education, which is accessible, convenient, and safe to practice skills because the methods of using curriculum setting programs and outcome of competencies vary.